Unexpected erosion-corrosion behaviour of 316L stainless steel produced by selective laser melting. (15th July 2019) - Laleh, Majid; Hughes, Anthony E.; Xu, Wei; Gibson, Ian; Tan, Mike Y.
Highlights: The erosion-corrosion of a SLM produced 316L SS was examined for the first time. SLM-produced 316L SS has shown lower than expected erosion-corrosion resistance. The unusual behaviour is due to the weak repassivation ability of SLM-produced 316L SS. Abstract: The erosion-corrosion behaviour of a near fully dense 316L stainless steel (316L SS), with relative density higher than 99.5%, produced by selective laser melting (SLM) has been evaluated, for the first time, in a jet impingement system. Although the SLM-produced 316L SS possessed superior pitting corrosion resistance and higher hardness, unexpectedly, it has shown lower erosion-corrosion resistance than its conventionally produced commercial counterpart. This behaviour has been related to weaker repassivation ability of the SLM-produced 316L SS mainly due to the presence of the SLM process-induced pores within the specimen.